Metformin exacerbates and simvastatin attenuates myelin damage in high fat diet‐fed C57BL/6 J mice. Issue 5 (19th August 2018) - Ciric, Darko; Martinovic, Tamara; Petricevic, Sasa; Trajkovic, Vladimir; Bumbasirevic, Vladimir; Kravic‐Stevovic, Tamara
Abstract : Diabetic neuropathy is one of the most deleterious complications of diabetes mellitus in humans. High fat diet (HFD)‐fed C57BL/6 J mice are a widely used animal model for type 2 diabetes mellitus and metabolic syndrome. We investigated the effects of metformin and simvastatin on the ultrastructural characteristics of sciatic nerve fibers in these mice. Metformin treatment increased the number of structural defects of the myelin sheet surrounding these fibers in already affected nerves of HFD fed mice, and simvastatin treatment reduced these numbers to the levels seen in control mice. These results warrant further research on the effects of metformin and statins in patients developing diabetic neuropathy and advise caution when deciding about optimal treatment modalities in these patients.